Mechanism Analysis on the Fluctuation of Linear Compressor in Refrigerator - Zou Huiming; Wang Min; Tang Mingsheng; Tian Changqing (Zhileng xuebao)
The experimental results of a refrigerator system with linear compressor showed that there was a period of piston stroke fluctuation as the supply power remained unchanged after an initial start-up adjustment. The maximum fluctuation rate of the piston stroke was 3.8% and that of the input power was 21.3%. The period of fluctuation was approximately 220 s. In this paper, the mechanism of this fluctuation is analyzed based on a simulation model set up for linear compressor. The fluctuation of the suction pressure is the dominant cause of stroke fluctuation. The fluctuation of the discharge pressure has little influence on the stroke fluctuation, while the stroke fluctuation has a significant effect on the discharge pressure. The fluctuation of the discharge pressure caused by the adjustment of the stroke control transfers to the suction part and causes the unstable fluctuation.